Clinical reassessment of denture fit and tissue tolerance in aging edentulous patients - Alfaer, Ali Salem; Alghamdi, Faris Ahmed; Alqahtani, Mohammed Dhafer; Alhassan, Atheer Ali; AlQahtani, Madawi Faraj; Alharbi, Khalid Fahad; Alshehri, Mohammed Abdullah; Alateeq, Abdulaziz Abdulsalam; Alamodi, Muaadh Hasan; Aldawsari, Saleh Mohammed; Alkhoofy, Osamh Fuad (International Journal Of Community Medicine And Public Health, 2026)
Tooth loss in the elderly remains a widespread concern, with complete edentulism significantly impacting oral function, comfort, and overall quality of life. As individuals age, ongoing anatomical and physiological changes in the oral cavity influence the performance of removable prostheses. Progressive alveolar bone resorption, soft tissue atrophy, and reduced neuromuscular coordination contribute to compromised denture retention and stability. In many cases, patients continue to wear their dentures for extended periods without reassessment, leading to tissue trauma, discomfort, and oral lesions. These problems are often exacerbated by age-related systemic health conditions, such as diabetes and dry mouth, which reduce the tissue’s capacity to adapt to mechanical pressure. Biological responses to long-term denture use vary significantly among patients, depending on factors like immune response, mucosal health, and hygiene practices. Tissue tolerance decreases when dentures are ill-fitting, unbalanced, or worn beyond their functional lifespan. Inflammatory conditions such as denture stomatitis and epulis fissuratum frequently emerge due to microbial colonization and sustained mucosal pressure. Clinicians must pay close attention to subtle tissue reactions and identify changes early to prevent chronic complications. Effective reassessment requires a comprehensive clinical approach that includes visual inspection, pressure distribution analysis, evaluation of occlusal function, and patient feedback. Corrective interventions may involve relining, occlusal adjustments, or complete prosthesis replacement. In complex cases, especially where tissue damage is advanced or retention cannot be restored by conventional means, implant-supported solutions may be explored. Continuous monitoring and patient-specific care are essential to ensure denture performance aligns with evolving anatomical and physiological conditions in the elderly. A proactive, structured reassessment strategy enhances comfort, protects soft tissues, and supports functional adaptation over time.